The end - Higson, Charles, 1958- (2016)
"The final battle ensues between Saint George's army of sickos and the army of London kids"--
"First published in Great Britain in 2015 by the Penguin Group."
Accelerated Reader AR
Keywords: Zombies -- Juvenile fiction; Survival -- Juvenile fiction; Horror stories; London (England) -- Juvenile fiction; Young adult fiction